2023
DOI: 10.26668/businessreview/2023.v8i2.923
|View full text |Cite
|
Sign up to set email alerts
|

The Enthusiasm of Digital Payment Services and Millennial Consumer Behaviour in Indonesia

Abstract: Purpose: This research aims to study the impact of changes in transaction styles in the 4.0 era with more depth, how consumers from various level start to use technology in ease of everyday life and consumer choices in the use of applications and their willingness to pay for the transaction fee, whether from bank institutions or digital start-up companies in terms of effectiveness, security, and public enthusiasm with digital payment technology.   Theoretical Framework: The framework was developed depend on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…In summary, the findings of this study align with the research conducted by Phuong Thanh Thi Tran et al (2023), highlighting the importance of "security" and "accurate transactions" as crutial attributes influencing consumers' decision to use digital banking services. While there is limited research on the impact of demographic characteristics on consumers' perception of digital banking service quality, previous studies by Gupta and Bansal (2011), Donthu and Garcia (1999), Dholakia et al (2004) and Kamal et al (2023) have also indicated the influence of age, gender, educational level, and other demographic factors on clients' perception and expectation of service quality.…”
Section: Factors Affecting Customers' Perception Of Digital Banking S...mentioning
confidence: 99%
“…In summary, the findings of this study align with the research conducted by Phuong Thanh Thi Tran et al (2023), highlighting the importance of "security" and "accurate transactions" as crutial attributes influencing consumers' decision to use digital banking services. While there is limited research on the impact of demographic characteristics on consumers' perception of digital banking service quality, previous studies by Gupta and Bansal (2011), Donthu and Garcia (1999), Dholakia et al (2004) and Kamal et al (2023) have also indicated the influence of age, gender, educational level, and other demographic factors on clients' perception and expectation of service quality.…”
Section: Factors Affecting Customers' Perception Of Digital Banking S...mentioning
confidence: 99%
“…At the heart of this transformation are mobile banking applications, which have become indispensable tools for modern financial transactions. With the ubiquity of smartphones, these applications not only offer unparalleled convenience but also a suite of functionalities that enable users to effortlessly transfer money, pay bills, open deposit accounts, and more, all from the comfort of their devices (Kamal et al, 2023).…”
Section: B Adoption Of Technology In Mobile Banking Applicationsmentioning
confidence: 99%
“…These factors are: (a) the resources and capabilities of firms, (b) business models, (c) networks and strategic partnerships, and (d) the market and environment. Many theorists like Barney (1991); Day (1994); Hamel and Prahalad (1990); Hunt (2013); Hooley, Broderick, and Möller (1998); Grant (1991); Kamal, Rizki, and Aulia (2023) and Prahalad and Hamel (1990) have immensely contributed to the theory of resource-based view, which provides the framework that a firm's strategic resources can help the firm achieve strategic advantages and accomplish its goals. Based on the theory of the resource-based view the study attempted to develop a multi-item scale for the four factors suggested by Soriano (2017) to measure digital financial inclusion in fintech firms.…”
Section: Introductionmentioning
confidence: 99%